Territorial planning and the prevention of natural disasters - Cruz Reyes, Fray Masías (1998)
To understand the problem of territorial planning and the prevention of natural disasters in the general context of the society in which we live, it is very important to be clear about the definitions of the categories related to these issues, which will allow us to understand the problem.